Effects of the COVID-19 pandemic on daily life, mental health and coping strategies in a subpopulation of Brazilian adolescents (Research, Society and Development, 2023)
The COVID-19 pandemic unprecedently impacted several aspects of people’s lives, including their mental health. Since adolescence confers vulnerability to mental health problems, this study aimed to analyze the impact of COVID-19 pandemic on daily life, mental health and coping strategies adopted by adolescents in Brazil and the correlation between these measurements. The study evaluated 215 adolescents from a Brazilian Middle and High school. A questionnaire to verify the impact of the pandemic on daily life aspects (academic activities, family/social interaction, and physical/mental health), the Depression, Anxiety and Stress Scale – Short Form (DASS-21), and the Coping Response Inventory – Youth Form (CRI-Y) were used. Results showed that the pandemic affected family/social interaction and physical/mental health aspects of life, in particularly among teenage girls. For this population, depression, anxiety and stress levels were also higher. A significant interaction between gender and educational stage was observed for the CRI-Y strategy “Acceptance or Resignation”, with girls, and in particularly older girls, punctuating more than boys. There was also a significant correlation between symptoms of depression, anxiety and stress and the following coping strategies: “Logical Analysis”, “Cognitive Avoidance”, “Acceptance-Resignation”, and “Emotional Discharge”. Results suggest that the pandemic significantly impacted different aspects of daily life and contributed to the increases in levels of depression, anxiety and stress in female adolescents and to the preferential use of maladaptive coping. These results highlight the urgent need for the development of effective intervention strategies, directed to stress coping, to mitigate the negative effects of COVID-19 in adolescents.